Preparing Future Computer Science Teachers to Work with Gifted Students. Computer-Based Implementation Technology - Soatmurodovich, Eshaliyev Utkir; Yuldoshovich, Turaev Tokhir (European Journal of Life Safety and Stability (2660-9630), 2021)
As our society develops, one of the most important tasks is to bring up young people in accordance with modern requirements. In particular, strengthening the work with gifted students is a key task in developing their talents, and training future computer science teachers.